2009
DOI: 10.1074/jbc.m806256200
|View full text |Cite
|
Sign up to set email alerts
|

Misfolding of Proteins with a Polyglutamine Expansion Is Facilitated by Proteasomal Chaperones

Abstract: Deposition of misfolded proteins with a polyglutamine expansion is a hallmark of Huntington disease and other neurodegenerative disorders. Impairment of the proteolytic function of the proteasome has been reported to be both a cause and a consequence of polyglutamine accumulation. Here we found that the proteasomal chaperones that unfold proteins to be degraded by the proteasome but also have non-proteolytic functions colocalized with huntingtin inclusions both in primary neurons and in Huntington disease pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Furthermore, PSMC5 unfolds proteins in a proteasomeindependent manner [e.g. transcription complexes or poly(Q) protein aggregates of Huntingtin] (Rousseau et al, 2009;Sun et al, 2002). Here, we provide compelling evidence that PSMC5 is an integral partner in the Shoc2 scaffolding complex.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, PSMC5 unfolds proteins in a proteasomeindependent manner [e.g. transcription complexes or poly(Q) protein aggregates of Huntingtin] (Rousseau et al, 2009;Sun et al, 2002). Here, we provide compelling evidence that PSMC5 is an integral partner in the Shoc2 scaffolding complex.…”
Section: Discussionmentioning
confidence: 78%
“…For studies in living cells we utilized the tagRFP (tRFP)-fusion protein of Shoc2 described in our earlier studies (Galperin et al, 2012). Given that overexpression of PSMC5 does not impair the function of the proteasome (Rousseau et al, 2009), we utilized a previously characterized fluorescently tagged PSMC5 (CFP-PSMC5) (Laporte et al, 2008). Fluorescence microscopy revealed that Shoc2-tRFP and CFP-PSMC5 are distributed in the cytosol ( Fig.…”
Section: Psmc5 and Shoc2 Colocalize On Late Endosomes And/or Mvbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfections were done with Lipofectamine 2000 (Invitrogen) and Dharmacon SMARTpool siRNA siGenome DNAJB6 (M-013020-00-0005) and non-targeting siRNA control siGENOME (D-001206- [13][14][15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…The proteasomal chaperones, Rpt4 and Rpt6 (AAA ATPase subunits of the 19S proteasomal particle), facilitated the aggregation of different expanded-polyQ disease proteins, huntingtin and ataxin-3, without affecting proteasomal degradation. 90 Furthermore, in vitro reconstitution experiments showed that purified 19S proteasomal particles enhanced aggregation of expanded-polyQ huntingtin protein. 90 Thus, a number of molecular chaperones can promote the assembly of disease proteins into amyloid-like aggregates.…”
Section: Chaperones Promote Aggregation Of Toxic Proteinsmentioning
confidence: 99%